Anisotropy of Ultrasonic Wave Velocities in Mizuho Cores - Yamada, Tomomi (1978)
P(論文) The snow cover at Mizuho Station (70°41′53″S, 44°19′54″E, 2230m in elevation), East Antarctica, is characterized by well-developed depth hoar. To clarify how the anisotropy of elastic wave velocities changes with densification process of the depth hoar having an anisotropic texture, the P- and the S-wave velocities were measured directly as a function of depth for both the vertical and the horizontal direction using the ultrasonic pulse method applied to deep core samples drilled to the depth of 145m at Mizuho Station. As for the P-wave velocity, the upper part of the ice sheet from the surface to the depth of 25-30m (0.72-0.73Mg/m^3 in density) was found to be anisotropic, while below that depth the ice sheet became isotropic. The curve of P-wave velocity versus density disclosed discontinuities at the densities of 0.65 and 0.84Mg/m^3,which correspond to the depths of 10∿16 and 55∿60m respectively. The latter depth corresponds to the level of the pore close-off. These three levels in the ice sheet were in fairly good agreement with the levels of discontinuities located on the density-depth curve. The facts indicate that the process of densification and metamorphism of snow and ice may change at these levels in the ice sheet at Mizuho Station. As for the S-wave velocity, the ice sheet was isotropic through all depths, whereas on the curve of S-wave velocity versus density only one discontinuity was clearly noticed, at the density of 0.65Mg/m^3. departmental bulletin paper